PENGARUH PROMOSI VIDEO MARKETING DAN KESADARAN MEREK DALAM MEMPENGARUI KEPUTUSAN PEMBELIAN KONSUMEN YAMAHA - Evi Maidasari; Vonny Tiara Narundana; Rina Lolyana (Universitas Bandar Lampung (UBL), 2021)
This research aims to find out the influence of video marketing promotion and brand awareness in influencing consumer purchasing decisions of Yamaha Motor Samples used by 60 respondents who are yamaha motor consumers working in PT. Yamaha taken using purposive sampling or judgement sampling techniques. The data used is primary data in the form of the dissemination of questionnaires in 60 respondents who are as consumers in PT. Yamaha. The analysis tool uses data quality test analysis tool in the form of validity test and reliability test, Classic Assumption Test, Determination Coefficient Test (R2), multiple linear regression, simultaneous test (F test) and partial test (t test). The results showed that the X1 variable (Video Marketing) and the X2 variable (Brand Awaseness) all statements or polls were declared valid and reliable, and passed the classic assumption test and all variables were declared to have a partial or simultaneous effect on variabl Y (Purchasing Decision).